Effects and mechanism of Lanthanum Citrate on the proliferation and apoptosis of hepatocellular carcinoma cell line SMMC-7721 - Bin Chen,; Zeming Hu,; Biao Chen,; Bofei Li, (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To investigate the effect and the possible mechanism of lanthanum citrate on the proliferation and apoptosis of human hepatocellular carcinoma (HCC) cell line SMMC-7721 through the Hedgehog (Hh) signaling pathway.Materials and Methods: Different concentrations of lanthanum citrate and KAAD-cyclopamine (the Hh signaling pathway representative inhibitor) were used to treat SMMC-7721 cells. Cell proliferation was detected using Methylthiazolyldiphenyl-tetrazolium bromide (MTT) assays. Cell apoptosis was detected using flow cytometry analysis of Annexin V-FITC/ propidium iodide (PI). The protein expressions of regulatory genes, such as cell cycle protein D1 (CyclinD1), cyclin-dependent kinase inhibitor 1 (p21), cysteinyl aspartate specific proteinase 3 (Caspase-3), B-cell lymphoma-2 (Bcl-2), glioma-associated oncogene homolog 1 (Gli1), and sonic hedgehog (Shh) were quantified using Western blot assays. The mRNA expressions of Gli1 and Shh were tested using quantitative real-time polymerase chain reaction (qRT-PCR) assays and the protein expressions of Gli1 and Shh were determined using immunofluorescence assays.Results: The Annexin V-FITC and PI double staining results revealed that the 0.1 mM lanthanum citrate group and the 15 µM KAAD-cyclopamine group had both increased the apoptosis rate of SMMC-7721 cells. Both lanthanum citrate and KAAD-cyclopamine downregulated the protein expressions of CyclinD1, Bcl-2, Gli1, and Shh and upregulated the protein expressions of p21 and Caspase-3. Additionally, the immunofluorescence results revealed that the protein expressions of Gli1 and Shh were significantly decreased in both the lanthanum citrate group and the KAAD-cyclopamine group compared to the control group.Conclusion: Lanthanum citrate inhibits proliferation and promotes apoptosis in HCC SMMC-7721 cells by suppressing the Hh signaling pathway.Cite this article as: Chen B, Hu ZM, Chen B, Li BF. Effects and mechanism of Lanthanum Citrate on the proliferation and apoptosis of hepatocellular carcinoma cell line SMMC-7721.Turk J Gastroenterol 2020; 31(3): 264-71.